(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A new larger foraminifer, Cuneospirella samnitica n. gen., n. sp., from the Santonian of the Matese Mountains (central Italy) is described. This taxon, characterized by an initial planispiral, a rectilinear adult stage and the subdivision of chambers by partitions, could be descended from a morphotype like Spiroplectammina multicamerata Said & Kenawy, recorded in the upper Turonian of the Apennines (central Italy).